In vitro antitumor activity of patulin on cervical and colorectal cancer cell lines - Mahdi Abastabar; Abolfazl Akbari; Javad Akhtari; Mohammad Taghi Hedayati; Tahereh Shokohi; hasan Mehrad-Majd; Hosseein Ghalehnoei; Sahar Ghasemi (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Patulin is a mycotoxin produced by some molds,especially Aspergillus and Penicilium, and is responsible for mycotoxicosis in animals and humans.There is still not very detailed data about the anti-cancer potency of patulin, but some reports demonstrated that it induces cellular apoptosis and toxicity. Materials and Methods: To determine the efficacy of patulin as a therapeutic strategy for cervical and colorectal cancers, we investigated its effects on HeLa,SW-48, and MRC-5 cell lines. Cell lines were exposed to various concentrations of patulin (i.e., 0.5, 1, 2, and 4 µM), then using methyl thiazolyl tetrazolium (MTT) and bromo-2′-deoxyuridine (BrdU) assays, the rates of apoptosis and cell viability were determined. Results: The obtained results showed a significant reduction in cell viability and apoptosis induction in a dose-dependent manner. Among all the cell lines, the highest growth inhibition rate was obtained at the 4 μM concentration of patulin.Conclusion: Our results suggested that patulin could significantly decrease tumor growth in human cervical and colorectal cancer models.